IMPLEMENTASI PROGRAM ASISTENSI MENGAJAR MBKM SEBAGAI MEDIA PEMBENTUKAN PROFESIONALISME CALON GURU SEKOLAH DASAR - Muhammad Nur Abdullah; Irjon Welem Kia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The shortage of professional teachers and the demand for improving the quality of basic education are crucial issues in the world of Indonesian education today. The MBKM Teaching Assistance Program comes as a strategic solution in shaping the professionalism of prospective elementary school teachers through direct involvement in the learning process at school. The purpose of this study is to show how the implementation of this program can improve the pedagogical, managerial, and social skills of prospective teachers. The method used in this research is descriptive qualitative method with participatory method conducted at SD Frater Thamrin Makassar through academic, non-academic, administrative, and community activities. The study process was carried out by reviewing activity documentation, logbooks, interviewing student teachers, and observing the implementation of learning directly. The expected results are the achievement of improved teaching skills, mastery of teaching tools, collaborative work experience with host teachers, and the formation of professional character in students.